Yogyakarta Urban Women: Expression Of Cultural Values Through Contemporary Jewelry In Experimental Installations And Live Performances - Hendranto, Dhyani (Sekolah Pascasarjana Institut Kesenian Jakarta, 2017)
Women have been seen as being capable in maintaining a spiritual and physical balance allowing them to exist as part of the community. Their harmonious spiritual, moral, intellectual and psychological achievements are a form of true perfection, and are desirable by every woman as represented by symbols which are considered to represent the ‘soul’ of Java urban women. The selected inspirational objects are packed to have meanings as well as aesthetic values and to deliver motivational, inspiring messages. The creation process of generating forms, structures, selections of color and material, and also movement, is the visual language that communicates the artists’ aspirations. This artwork shows the artist’s creative characters; essentially every human being has creative potentials that could lead to the finding of his or her own original personal concepts that would eventually give birth to innovative and varied artworks. The theme of women who are members of our community possesses the potential to be expanded broadly, so that it will become a priority issue and that it will receive due attention, as women are a major stakeholder in the continuity of humanity. The way women struggle to achieve balance, in the midst of existing values and stereotyping is a remarkable feat, and the artist, as a woman, tries to visualize all their feelings in the creation of this work. Perempuan dipandang mampu menjaga keseimbangan spiritual dan fisik, sehingga mereka dapat eksis sebagai bagian dari masyarakat. Pencapaian spiritual, moral, intelektual, dan psikologis mereka adalah sebentuk kesempurnaan yang nyata dan merupakan suatu hal yang diinginkan setiap perempuan sebagaimana ditampilkan dengan simbol-simbol yang dianggap merepresentasikan ‘jiwa’ perempuan urban Jawa. Obyek-obyek inspiratif yang dipilih dianggap memiliki makna serta nilai estetika, serta mampu menyampaikan pesan-pesan motivasional dan menginspirasi. Proses penciptaan bentuk dan struktur, pemilihan warna serta material, serta bentuk, adalah bahasa visual yang menyampaikan aspirasi sang seniman. Karya seni menampilkan sifat seorang seniman dengan sangat jelas. Pada dasarnya setiap manusia memiliki potensi kreatif yang mampu menciptakan karya seni yang inovatif dan berbeda- beda. Tema peran perempuan dalam masyarakat perlu diperluas agar menjadi isu prioritas dan mendapat perhatian yang diperlukan, karena perempuan adalah stakeholder besar dalam kelanjutan kemanusiaan. Cara perempuan menciptakan keseimbangan, di tengah-tengah nilai yang sudah ada dan stereotyping, sangat menakjubkan dan sang seniman, sebagai seorang perempuan, mencoba untuk memvisualisasikan seluruh perasaannya dalam penciptaan karya ini.